Sekolah Ramah Anak Berbasis Pesantren: Integrasi Pendidikan Karakter dan Nilai-Nilai Religius - Al Rosid, Moh. Harun; Wakhid, Lutfi; Nasikhatul Murtafi'ah, Aniq; Septiana, Nani (Fakultas Tarbiyah dan Ilmu Keguruan UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
The concept of a child-friendly school based on Islamic boarding schools is an integration of character education and religious values ​​of Islamic boarding schools. This study aims to analyze the concept and implementation of a child-friendly school based on Islamic boarding schools. The approach to this research is qualitative while the design is a case study. The location of the research is at the Darussalam Islamic Boarding School Blokagung Banyuwangi. Research is the key instrument of the research. The subjects of the research are the head of education, principal, vice principal, teachers, and students. Determination of informants using purposive and snowball sampling. Data collection techniques are participant observation, in-depth interviews and document studies. Data analysis using the interactive model of Miles, Huberman, and Saldana theory, namely data condensation, data presentation, and drawing conclusions. Data validity testing uses credibility, dependability, and confirmability tests. Data validity is checked continuously, triangulation, member checking, peer discussion, and reference checking. The research findings are the implementation of child-friendly schools based on Islamic boarding schools through the formulation of policies through the head of education and teaching, principal, and vice principal, provision of facilities and infrastructure, educators and education personnel who understand and are certified and trained in children's rights, involvement of students to actively participate in the development of talents and interests, involvement of parents, alumni and the community, and learning with a fun, active, integrated concept known as recreational learning.